Natural regulatory anticoagulants proteins among Sudanese patients with dengue virus infection - Bashir, Bashir Abdrhman; Saeed, Osman Khalaf Allah (International Journal of Health Sciences, 2017)
The Coagulation System: Abnormalities in natural physiologic anticoagulants are observed in dengue infection. Laboratory values such as protein C (PC), protein S (PS), and antithrombin (AT) indicate this problem on the coagulation system in dengue. Recently, an interrelationship between dengue and the levels of natural anticoagulants has been observed. Objective: The study conducted to find out the effect of dengue on the natural anticoagulant proteins. Methods: A case–control study was conducted in Port Sudan Teaching Hospital from February 2013 to June 2014 for 334 cases of dengue caused by dengue virus, 217 (65%) males and 117 (35%) were females along with 101 cases of control 64 (63.4%) males and 37 (36.6%) were females. Laboratory-positive dengue cases were confirmed by immunoglobulin (Ig) M and IgG immune chromatography rapid test and the WHO criteria were used for classifying the dengue severity. Platelet count (PLT), plasma prothrombin time (PT), partial thromboplastin time (PTT), fibrinogen, D-dimer (DD), aspartate transaminase, alanine transaminase, PC, PS, and AT were performed. Results: Of 334, 289 patients had dengue fever (DF) and 45 patients had dengue hemorrhagic fever (DHF). Thrombocytopenia was present in 279 (83.5%). PLT was found to be significantly low in the case of dengue (P < 0.000). There was a highly significant difference between the prolongations of PT and PTT in DF (P < 0.000). Prolongations of PT and PTT were significantly higher (90% and 76.2%, respectively) in DF than DHF patients (10% and 23.8%, respectively). PC and PS were significantly higher in DHF 100% and 80% than DF 89% and 57%, respectively. Conclusion: The findings of this study suggest that lower levels of these proteins in patients with dengue are attributed to disseminated intravascular coagulation.